Still marginalized: Gender inequalities in the largest Polish daily’s sports coverage - Zbigniew, Dziubiński and Organista, Natalia and Mazur, Zuzanna (Communications, 2019)
Abstract The studies conducted over recent decades on media sports coverage indicatedmajor underrepresentation of women’s sports. The underrepresentation of women’s sports in the media is aligned with the perception of sport as a masculine construct with sportswomen as the ‘other’. However, most studies were conducted in English-speaking countries. In this article we present our findings of press media coverage in Poland. The aim of the study was to provide an analysis of sports press coverage in the largest Polish daily, Gazeta Wyborcza, with respect to gender inequality. The chosen method was content analysis. The results show an underrepresentation of women’s sports in the examined press coverage – only 12.5% of all articles concerned female sports. Qualitative analysis demonstrates that the articles differed in terms of the athletes’ gender as well. The study highlighted the gender-dependent nature of the examined sports press coverage in Poland.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9jb21tdW4tMjAxNy0wMDQ3